The dermoscopic manifestation of nail pigmentation - Hanar Ahmed Khidhir; Mohammed Yousif Saeed (Advanced Medical Journal)
Background and objectives: Nail pigmentations are of diagnostic challenging for dermatologists, as they may be involved in many local and systemic diseases that difficult to diagnose clinically. Our aim is to assess the specific dermoscopic features of different pigmented nail lesions.